Wizerunki polityczek w Internecie. - Troszyński, Karol (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2020)
In this article I’m trying to find the answer to question “How is create the image of politicians?” The main platform of communications politicians with voters in my study was a social media. The study lasted three weeks. Time of the survey included two weeks of polish parliamentary campaign in 2015 and one Christmas week. In this time I analyzed 30 randomly selected politicians, who had their own profile on Facebook. I analyzed only a woman-politicians.